Controversial Encounters in the Age of Algorithms : How Digital Technologies Are Stifling Public Debate and What to Do About It - Sine N. Just (Bristol University Press, 2025)
How can we have meaningful public conversations in the algorithmic age? This book explores how digital technologies shape our opinions and interactions, often in ways that limit our exposure to diverse perspectives and fuel polarization. Drawing on the ancient art of arguing all sides of a case, the book offers a way to revive public debate as a source of trust and legitimacy in democratic societies. This is a timely and urgent book for anyone who cares about the future of democracy in the digital era.